Model Materi Ajar Kitabah Arabiyah Berbasis Pendekatan Proses Genre di Perguruan Tinggi - Samsi Setiadi; Zainal Rafli (Universitas Negeri Jakarta, 2017)
This study aims to obtain a model of teaching materials of Arabic writing (kitabah Arabiyah) based on the genre process approach at the State University of Jakarta. The method used is the development research to obtain the model of Arabic writing materials based on the genre process approach. The results showed that students still had difficulties at a fairly high level, such as finding key ideas, developing paragraphs, applying appropriate Arabic rules, finding and selecting the vocabularies that fit the context of the sentence. Students make some mistakes when writing Arabic script, including incorrect writing of letters, selection of verb (fi’il) and noun (isim), mistakes of intended meaning, incomplete sentences, and incomplete paragraphs. The need of students to the learning of Arabic writing shown by the scores of students' needs on the study is 3.90 which means that Arabic writing teaching is needed. The development of Arabic-based teaching material model based on the genre approach is needed as an alternative to problem solving.